2009
DOI: 10.1364/ol.34.002613
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic strain measurement in optical fibers by stimulated Brillouin scattering

Abstract: We present a technique for dynamic strain measurements in optical fibers based on the stimulated Brillouin scattering interaction between two counterpropagating optical pulses. The technique allows for a high sampling rate and permits to addressing dynamically and randomly the position at which vibration is measured. Preliminary experimental results carried out with a perturbation frequency up to 98 Hz demonstrate the validity of the proposed technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
134
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(134 citation statements)
references
References 4 publications
0
134
0
Order By: Relevance
“…Therefore, the BGS effectively acts as a frequency discriminator which converts variations in the Brillouin frequency shift (BFS) to changes in the optical power. Using this technique, Bernini et al 36 The strain range of the SA-BOTDA technique demonstrated by Bernini et al, however, is limited to less than half the Brillouin gain spectrum linewidth and cannot be implemented if there are larger variations in the BFS along the sensing fibre. Peled et al 37 introduced an alternative method to solve this problem by adjusting the optical frequency of the pump.…”
Section: B Brillouin Optical Time Domain Analysis (Botda)mentioning
confidence: 99%
“…Therefore, the BGS effectively acts as a frequency discriminator which converts variations in the Brillouin frequency shift (BFS) to changes in the optical power. Using this technique, Bernini et al 36 The strain range of the SA-BOTDA technique demonstrated by Bernini et al, however, is limited to less than half the Brillouin gain spectrum linewidth and cannot be implemented if there are larger variations in the BFS along the sensing fibre. Peled et al 37 introduced an alternative method to solve this problem by adjusting the optical frequency of the pump.…”
Section: B Brillouin Optical Time Domain Analysis (Botda)mentioning
confidence: 99%
“…Brillouinbased distributed optical fibre sensors (DOFS) measure the absolute strain and temperature along the fibre using the Brillouin frequency shift (Bernini 2009 andPeled 2011). Although this class of sensors have a higher strain range, their applications as a dynamic strain sensor are limited to short sensing ranges due to the negative trade-off between the frequency and sensing range (Masoudi 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of BOTDAs has been improved with contributions in different areas: from the increase in the sensing length, for example via Raman 1 or Brillouin assistance 2 , to the achievement of higher spatial resolutions 3 or the ability to perform dynamic measurements 4 . In fact, a figure-of-merit (FoM) has been proposed 5 , enabling a tool to compare the performance of different BOTDA implementations.…”
Section: Introductionmentioning
confidence: 99%